1991
DOI: 10.1080/0028825x.1991.10416718
|View full text |Cite
|
Sign up to set email alerts
|

Growth ofPinus radiatain relation to foliar element concentrations on ultramafic soil, New Zealand

Abstract: Nine-year-old Pinus radiata in a plantation on ultramafic soil at Black Ridge, Southland, vary greatly in size. Four measures of growth (Iree height, basal diameter, and dwarf shoot size and weight) were recorded in 50 plants, together with concentrations of 18 elements in current-year foliage. Correlation coefficients and multiple regression of element concentrations against tree height indicated that phosphorus, potassium, copper, and nitrogen were the main elements influencing Pinus radiata growth on this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Foliar nutrient concentration has been widely used as an index of diagnosis of tree nutrition, since foliar nutrient concentration is highly correlated with tree growth and soil nutrient availability (Lee et al, 1991;Elias et al, 2002;Hobbie and Gough, 2002). However, this is not universal and many studies found that total foliar N and P concentrations remained constant with tree growth (Vitousek et al, 1995;Aerts and Chapin, 2000;Thomas et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Foliar nutrient concentration has been widely used as an index of diagnosis of tree nutrition, since foliar nutrient concentration is highly correlated with tree growth and soil nutrient availability (Lee et al, 1991;Elias et al, 2002;Hobbie and Gough, 2002). However, this is not universal and many studies found that total foliar N and P concentrations remained constant with tree growth (Vitousek et al, 1995;Aerts and Chapin, 2000;Thomas et al, 2006).…”
Section: Introductionmentioning
confidence: 99%